Diary of a Child Called Souad - Saadawi, Nawal El.; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
Diary of a Child Called Souad is Nawal El Saadawi's first autobiography, written at the age of ten in the form of fiction as she explores her early awakening to the world around her. Now known for her bold spirit and probing mind, El Saadawi in this novel uncovers through a child's eyes the hypocritical values and traditions carried on by family, education, religion, and society. With amazing courage she weaves a tale of the fear, guilt, and repressive compliance forced upon her as a woman and upon her generation as the price to be paid for leading a civilized existence. Struggling to come to terms with taboos concerning her maturing body, the young Nawal's writing reveals the makings of a revolutionary spirit and relentlessly analytical mind. A must read for devotees of El Saadawi's writing to witness an early record of the maturing of her thoughts and the shaping of her ideas.
Keywords: Middle Eastern literature; Fiction; Childhood, Adolescence and Society